Some Sharpening and Generalizations of a Result of T. J. Rivlin (Analysis in Theory and Applications, 2017)
Let $p(z)=a_0+a_1z+a_2z^2+a_3z^3+…+a_nz^n$ be a polynomial of degree $n$. Rivlin [12] proved that if $p(z) eq 0$ in the unit disk, then for $0< r≤ 1,$ $${\max_{|z|=r}|p(z)|}≥ \Big(\dfrac{r+1}{2}\Big)^n{\max_{|z|=1}|p(z)|}.$$ In this paper, we prove a sharpening and generalization of this result and show by means of examples that for some polynomials our result can significantly improve the bound obtained by the Rivlin's Theorem.
Keywords: Inequalities; polynomials; zeros.